PENGGUNAAN LAMPU ROTATOR OLEH SATPOL SATUAN POLISI PAMONG PRAJA DI KOTA JAMBI BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Relita Putri Ayu; Sayuti Sayuti; Burhanuddin Burhanuddin (Tazir, 2024)
This journal aims to increase public understanding about the use of rotator lights by the Jambi City Satpol PP. Among them are the provisions for the use of rotator lights by the Satpol PP according to law number 22 of 2009 concerning road traffic and trasportation and the level of effectiveness of the use of rotator lights by the Jambi City Satpol PP. this journal uses a legal sociology approach with data collection methods through observation, interviews and documentation. Based on the research conducted, the following results and conclusions were obtained: 1) the use of rotator lights by Satpol PP is regulated in law number 23 of 2014 concerning government, further provisions regalding Satpol PP are regulated in government regulation numer 16 of 2018 concerning police units. Civil service. Law numer 22 of 2009 concerning road traffic and transportation does not clearly regulate the use of rotator lights by satpol PP but only regulates generally the procedures for traffic. 2) the rotator ligh used by the jambi city Satpol PP is very effective in carrying out tasks when in an urgent situation because this rotator light can be a notification for the public to know that when the rotator ligh is turned on that there is a very critical situasion that needs to proritized. Keywords: effectiveness, rotator lights, civil service police unit